2020
DOI: 10.1155/2020/1602816
|View full text |Cite
|
Sign up to set email alerts
|

Irvingia gabonensis Seed Extract: An Effective Attenuator of Doxorubicin-Mediated Cardiotoxicity in Wistar Rats

Abstract: Cardiotoxicity as an off-target effect of doxorubicin therapy is a major limiting factor for its clinical use as a choice cytotoxic agent. Seeds of Irvingia gabonensis have been reported to possess both nutritional and medicinal values which include antidiabetic, weight losing, antihyperlipidemic, and antioxidative effects. Protective effects of Irvingia gabonensis ethanol seed extract (IGESE) was investigated in doxorubicin (DOX)-mediated cardiotoxicity induced with single intraperitoneal injection of 15 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 76 publications
1
15
0
Order By: Relevance
“…The activities of endogenous antioxidant enzyme systems consisting of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) were estimated with spectrophotometry separately. Heart tissue homogenates were prepared to detect MDA levels, CAT, SOD, and GSH-Px activities 22 strictly according to the instructions provided with the kits (Jiancheng, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The activities of endogenous antioxidant enzyme systems consisting of catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) were estimated with spectrophotometry separately. Heart tissue homogenates were prepared to detect MDA levels, CAT, SOD, and GSH-Px activities 22 strictly according to the instructions provided with the kits (Jiancheng, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition of Irvingia gabonensis ethanol seeds extract was reported by Olorundare and coworkers in 2020 [13] and it was revealed that 4,6-di-O-methyl-alpha-dgalactose, Neophytadiene, 4-Methyl-2,5dimethoxybenzaldehyde, Cycloheptasiloxane, tetradecamethyl-, Pyrrolidine, 1-(1-cyclohexen-1yl)-, Naphthalen-4a,8a-imine, octahydro-, Cyclotetrasiloxane, octamethyl-, Z,Z-7,11-Hexadecadien-1-ol, Cyclotetrasiloxane, octamethyl-,1,2-Cyclopentanedione, Ethanol, 2-(ethylamino)-and Oxime-, methoxy-phenyl-were the common compounds. While quercetin, kaempferol, ellagic acid, mono-, di-, and tri-Omethyl-ellagic acids, and their glycosides were reported earlier [6,14].…”
Section: Introductionmentioning
confidence: 79%
“…[28] Pisum sativum peel or Irvingia gabonensis seed extract were also candidates as natural agents to protect against Dox toxicity. [29,30] However, the juice or extract was generally given at a high dose (up to 500 mg/kg bodyweight per day). Although this is close to dietary intake, it's difficult to clinically translate.…”
Section: Discussionmentioning
confidence: 99%